2022
DOI: 10.1111/febs.16326
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α/ENO1 signaling facilitates testicular phagocytosis by directly activating Elmo1 gene expression in mouse Sertoli cells

Abstract: Phagocytic clearance of apoptotic germ cells (GCs), as well as residual bodies released from developing spermatids, is critical for Sertoli cells (SCs) to maintain inner environment homeostasis within the testis. However, the molecular mechanisms controlling the phagocytosis are ill defined. Here, we identify a new role for alpha‐enolase (ENO1), a key enzyme during glycolysis, as a molecule that facilitates testicular phagocytosis via transactivation of the engulfment and cell motility 1 (Elmo1) gene. Using im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Notably, we found that the key protein P19140 (Alpha-enolase) could control the semen quality of drakes by regulating the expression of apoptosis-related proteins. A previous study has shown that downregulating Alpha-enolase ( ENO1 ) expression via small RNA interference resulted in the disturbance of spermatogenesis through apoptosis ( Xiong et al, 2021 ). In another research, the finding showed that Alpha-enolase expression ( ENO1 ) was correlated with sperm motility ( Li et al, 2016 ).…”
Section: Disscusionmentioning
confidence: 99%
“…Notably, we found that the key protein P19140 (Alpha-enolase) could control the semen quality of drakes by regulating the expression of apoptosis-related proteins. A previous study has shown that downregulating Alpha-enolase ( ENO1 ) expression via small RNA interference resulted in the disturbance of spermatogenesis through apoptosis ( Xiong et al, 2021 ). In another research, the finding showed that Alpha-enolase expression ( ENO1 ) was correlated with sperm motility ( Li et al, 2016 ).…”
Section: Disscusionmentioning
confidence: 99%